Determination of elastic constants of transition metal oxide based thin films using surface brillouin scattering - Ayele, Fekadu Hailu (My University, 2016)
Bismuth ferrite BiFeO3 is a transition metal oxide that exhibits both antiferromagnetic and ferroelectric orderings and is termed a magnetoelectric multiferroic. These functional properties make it crucial for applications in various nanoelectronic devices and sensors. However, the integration of BiFeO3 in devices requires the scaling down of bulk BiFeO3 to nano dimensional length scales in thin lm format. For this purpose, the elements of the elastic constant tensor of BiF eO3 thin lms are requisite, especially in multilayered or single layer-on-substrate device con gurations. It is thus essential that mechanical properties of BiFeO3 thin lms be established due to their size and growth mode dependence. Therefore, the study aims to determine the propagation of the surface acoustic waves and the elastic constants of BiFeO3 BFO thin lms in order to tailor the mechanical properties for device applications. In this approach the e ect of morphology and microstructure on the elastic constants has been investigated.
A dissertation submitted to the Faculty of Science, Wits University, in fulfilment of the requirements for the degree of Master of Science. 30 March 2016.
Keywords: Metal oxide semiconductors; Metal oxide semiconductors field-effect transistors; Brillouin scattering